The Effectiveness of Implementing Local Wisdom-Based Chemistry Learning Modules in High Schools to Increase Students' Interest In Learning: A Systematic Review - Mubarak, Syarifatul; Juliani, Iis; Safitri, Intan; Hayati, Nazlia; Yuliani, Rani (Islamic Journal of Integrated Science Education (IJISE), 2026)
This study aims to analyze the effect of implementing local wisdom-based chemistry learning modules in high school on students' learning interest. Local wisdom is a part of culture in society that can be integrated into chemistry learning to make the material more contextual and relevant to students' daily lives. Attractive and relevant modules can enhance students’ comprehension, motivation, and potential. The research method used is the Systematic Literature Review (SLR), in which data were collected from articles indexed in Google Scholar articles indexed on the SITA page. Of 387 articles, 35 met the criteria and were fully accessible for analysis. The results of the study indicate that implementing local wisdom-based modules that are interesting and systematically designed can improve students’ interest in learning. This study concludes that integrating local wisdom into chemistry learning not only improves comprehension of the material but also fosters students' love and concern for local culture.